Uma brasileira: a outra história de Julia Mann - Miskolci, Richard [UNESP] (Núcleo de Estudos de Gênero - Pagu, 2003)
O texto parte da recente valorização da origem brasileira de Julia Mann, a matriarca da célebre família de escritores alemães, para discutir o tema da nacionalidade associado às categorias de gênero e raça. Discutimos a historicidade de categorias sociais e como estas determinam a auto-compreensão dos indivíduos. A sociedade alemã do século XIX caracterizou Julia como brasileira e, apesar do estigma que isto representava, ela utilizou-se desta origem exótica como forma de autocompreensão e resistência.

Julia Mann was the matriarch of the famous family of German writers. This paper uses the recent interest in her Brazilian origin to discuss the theme of nationality associated with categories of gender and race. We show the historicity of social categories and the way they determine the self-understanding of individuals in a specific time. Nineteenth century German society characterized Julia as a Brazilian and, despite the stigma this category brought along with it, Julia used this exotic origin as a way for her self-understanding and for her resistance to the racist society in which she lived.
A brazilian woman: the other history of Julia Mann
Keywords: Julia Mann; Gênero; Nacionalidade; Raça; Cidadania; Julia Mann; Gender; Nationality; Race; Citizenship